Design, synthesis and antitumor activities of fluoroquinolone C-3 heterocycles (IV): s-triazole Schiff-Mannich bases derived from ofloxacin - Guoqiang Hu; Guoqiang Wang; Nannan Duan; Xiaoyi Wen; Tieyao Cao; Songqiang Xie; Wenlong Huang (Elsevier, 2012)
The aim of this research was to produce novel antitumor fluoroquinolones from antibacterial analogs by introduction of a heterocyclic ring as a bioisostere of the C-3 carboxylic acid group. To this end, two series of eleven s-triazole derivatives bearing functionalized side chains of Schiff bases and Schiff-Mannich bases were designed and synthesized. Structures were characterized by elemental analysis and spectral data after which in vitro antitumor activity against L1210, CHO and HL60 cell lines was evaluated in the MTT assay. Compounds possessing a free phenol group were particularly active and warrant further development.